Rural poverty monitoring survey, April 1996. - Bangladesh. Parisaṃkhyāna Byuro; Regular and Continuous Monitoring of Poverty Situation in Bangladesh Project (Dhaka : Bangladesh Bureau of Statistics, Statistics Division, Ministry of Planning, Govt. of People's Republic of Bangladesh, 1998)
With reference to Bangladesh.
"Regular and Continuous Monitoring of Poverty Situation in Bangladesh."
Keywords: Rural poor -- Bangladesh; Rural poor -- Bangladesh -- Statistics; Household surveys -- Bangladesh